UPAYA MENGATASI NYERI PUNGGUNG BELAKANG DAN MENINGKATKAN KUALITAS TIDUR IBU HAMIL TRIMESTER III MELALUI PEMBERIAN BACK RUB - Sri Ningsih, Ningning; Nawati; Pursitasari, Ita (Jurnal Pengabdian Masyarakat Kesehatan Indonesia, 2024)
Pregnancy in the third trimester start from 28 weeks to 40 weeks of gestation. Every semester there are changes that occur due to hormonal imbalances. Change that occur in mothers often cause discomfort, namely back pain and sleep quality problems caused by changes in body posture, this is in line with the gradual increase in body weight during pregnancy and redistribution of ligaments, the body’s center gravity shifts forward and when combined with stretching of the abdominal muscles which weak in pregnancy womwn when begin during the pregnancy process. As the gestational age increase, there will also be complaint, an increasingly enlarge stomach, back pain, difficulty in starting to sleep, fatique and physiological canges such as increasing levels of progesterone and prolactin, so that this sleep disturbsnces will affect the quality of sleep. Cadres” knowledge has increased and Bac Rub is an intervention to treat back pain and sleep disorders. Result there was an effect of giving back rub on back pain and sleep quality of pregnant women in the third trimester. Recommendation : Back Rub be used as an alternative intervention and included in Community Health Center Programs, especially for pregnant women.